The Effects of Intraperitoneal Sildenafil Administration on Healing of Left Colonic Anastomoses and Intra-Abdominal Adhesion Formation in the Presence of Intra-Abdominal Infection - Ayten, Refik; Cetinkaya, Ziya; Girgin, Mustafa; Ozercan, Ibrahim; Ustundag, Bilal; Aygen, Erhan (Lippincott Williams & Wilkins, 2008)
PURPOSE: The objective of this pilot study was to establish an animal model for intra-abdominal infection and to examine the effect of sildenafil on anastomotic healing of the left colon and intra-abdominal adhesion formation. METHODS: Fourteen Winstar rats underwent colonic transsection and primary anastomosis after performing intra-abdominal infection. Rats were divided into two groups: Group 1 (n=7): intra-abdominal infection, resection, and anastomoses; Group 2 (n=7): intra-abdominal infection, resection, anastomoses, and sildenafil. Anastomotic bursting pressures, hydroxyproline levels, histopathologic grading, and abdominal adhesions were accessed on the postoperative Day 7. RESULTS: Anastomotic healing was found to be improved in terms of a bursting pressure (P=0.02). Histopathological examination revealed an increase in angiogenesis (P=0.007). Moreover, intra-abdominal adhesions were significantly less in rats given sildenafil (P=0.03). CONCLUSION: Sildenafil may improve anastomotic healing of the left colon and diminishes peritoneal adhesion formation in the presense of abdominal infection.
Keywords: Intra-abdominal infection; Left colonic anastomoses; Peritoneal adhesion; Sildenafil